Tourism Student’s Perceptions of Career in the Tourism Industry: study of Indonesian and thai students - Alika Suryadini; Yeni Yuniawati; Oce Ridwanudin (Universitas Pendidikan Indonesia, 2024)
The aim of this research is to analyze the differences in opinions of two groups, Thai students and Indonesian students regarding careers in the tourism industry. This research determines whether one group is more committed to a career in industry than another group. The approach in this research uses quantitative descriptive with survey methods. The research results show that there are significant differences between the two groups, especially when comparing their responses to careers in the tourism industry. From these results it is said that Thai students are more likely to believe that background can influence interactions and relationships between colleagues and guests in the tourism industry, while Indonesian students are more likely to be satisfied after working in the tourism industry and committed to continuing their career in the tourism industry after graduating. In addition, it was found that students' perceptions of careers in the tourism industry were much more positive than previous research. This has implications for tourism entrepreneurs because it shows that students have a positive perception of the industry. So, there is a greater possibility of joining this industry after graduation.